1983
DOI: 10.1161/01.cir.67.1.216
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in chronic aortic insufficiency. Is valve replacement too late when left ventricular end-systolic dimension reaches 55 mm?

Abstract: SUMMARY To determine whether a ventricular (LV) end-systolic dimension (ESD) > 55 mm and LV left fractional shortening < 25% are risk factors for aortic valve replacement (AVR) in patients with aortic insufficiency, we analyzed the clinical course and M-mode echocardiograms in 47 consecutive patients who underwent AVR for isolated symptomatic Al. Group 1 patients (n = 27) had a preoperative ESD < 55 mm (mean 44 mm, range 30-52 mm) and group 2 patients (n = 20) had a preoperative ESD > 55 mm (mean 62 mm, range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…For late morbidity after AVR, earlier studies have provided either no 4,7,15 or limited information. 8,16 Even in studies with data on morbidity, specific information is not available about patients with markedly reduced EF. 8,16 In our study, long-term morbidity after AVR is dissociated in the subgroup with LoEF, increased for heart failure, but similar for thromboembolism.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For late morbidity after AVR, earlier studies have provided either no 4,7,15 or limited information. 8,16 Even in studies with data on morbidity, specific information is not available about patients with markedly reduced EF. 8,16 In our study, long-term morbidity after AVR is dissociated in the subgroup with LoEF, increased for heart failure, but similar for thromboembolism.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationsmentioning
confidence: 99%
“…8,16 Even in studies with data on morbidity, specific information is not available about patients with markedly reduced EF. 8,16 In our study, long-term morbidity after AVR is dissociated in the subgroup with LoEF, increased for heart failure, but similar for thromboembolism. Therefore, our study establishes for the first time that patients with markedly reduced EF and severe AR represent a high-risk group even after successful AVR.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationsmentioning
confidence: 99%
“…Over the two last decades 5,6 , clinical trials were based primarily on LV dimensions and systolic function as indications of the ideal timing for aortic valve replacement. This procedure interrupts the natural history of AR, but it exposes the patient to the risks of surgery and valve prosthesis implantation.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,23 Some surgical studies, however, have suggested that this parameter is too restrictive, based on the postoperative course of symptomatic and asymptomatic patients. 20, 24 Also, compared with exercise parameters, these parameters are relatively insensitive. 19,24 Therefore, although baseline LVESD is used to guide the timing of AVR, baseline LVESD cannot fully detect delayed LV dysfunction and postoperative LV dysfunction in severe AR.…”
Section: Early Detection Of LV Dysfunction In Armentioning
confidence: 99%